Using dynamic content to increase relevance - Matsyi, Olha; Маций, Ольга Борисівна; Маций, Ольга Борисовна (Харківський національний автомобільно-дорожній університет, 2021)
This article explores the process of using dynamic content to increase the relevance and conversion rate of a web resource. The main advantage of this approach is that it does not require the creation of additional pages of the site, increases the relevance of the content and, consequently, the likelihood of obtaining the effect of conversion.
Використання динамічного контенту для підвищення релевантності
Использование динамического контента для повышения релевантности
Keywords: contextual advertising; traffic analysis; conversion; relevance; веб-сайт; інтернет-маркетинг; аналіз трафіку; конверсія; релевантність; интернет-маркетинг; анализ трафика; конверсия; релевантность; 004.9; 10.30977/BUL.2219-5548.2021.92.1.34